Seismic energy response analysis of equipment-structure system via real-time dynamic substructuring shaking table testing. Issue 1 (January 2020) - Bi, Jihong; Luo, Lanfang; Jiang, Nan
Dynamic equations are presented that have been deduced for a real-time dynamic substructuring shaking table test of an equipment-structure system, based on the branch mode substructure method. The equipment is adopted as the experimental substructure, which is loaded by the shaking table, while the structure is adopted as the numerical substructure. Real-time data communication occurs between the two substructures during the test. A real-time seismic energy calculation method was proposed for the calculation of energy responses, both in the experimental substructure and the numerical substructure. Taking a representative four-story steel frame/equipment model, real-time dynamic substructuring shaking table tests and overall model tests were executed. The proposed real-time dynamic substructuring shaking table testing method was verified by comparing the test results with shaking table test results for the overall model. The energy responses of each component in the equipment-structure system, using different connection types, also were studied. Changes in the connection types can lead to changes in the energy responses of the equipment-structure system, especially with respect to the equipment. The choice of the connection for the equipment-structure coupled system should take into account the operational performance objective of the equipment.